2019
DOI: 10.3390/cleantechnol1010011
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of an ASHP System Using Waste Air to Recover Heat Energy in a Subway System

Abstract: In this short communication, we demonstrate that the performance of a typical air source heat pump (ASHP), exploiting a relatively stable air temperature within a subway environment, is high, even during the peak heating months. After a nine-month operational run, the coefficient of performance is demonstrated to be 3.5. The design and installation difficulties are stated together with the lessons learnt following this trial. The actual energy and carbon savings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The study showed not only the financial benefits, but also the energy and carbon reduction of this trial. The authors in [39] demonstrated that the performance of a typical air source heat pump (ASHP), exploiting a stable air temperature within a subway environment is high, even during the peak heating months.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed not only the financial benefits, but also the energy and carbon reduction of this trial. The authors in [39] demonstrated that the performance of a typical air source heat pump (ASHP), exploiting a stable air temperature within a subway environment is high, even during the peak heating months.…”
Section: Introductionmentioning
confidence: 99%
“…They can transfer heat from natural resources in the human environment, such as air, ground, and water, as well as from sources like industrial or domestic waste [1]. Current research is largely focused on hybrid systems that use heat pumps in combination with solar collectors (SC) or photovoltaic panels (PV) [8][9][10][11][12][13][14], as well as on recovering waste heat and raising its temperature to more useful levels [15][16][17][18][19]. Such solutions allow the increase of energy and economic efficiency of heating and cooling rooms, while bringing significant benefits to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ninikas et al [17] showed the outcome of a trial heating system using waste resources and the importance of a primary energy saving in Glasgow using a water source heat pump (WSHP). In another study [18], Ninikas et al discussed the benefits of an ASHP system for Glasgow. The performance of a typical air source heat pump could be increased significantly in relatively stable air temperature and humidity conditions [19].…”
Section: Introductionmentioning
confidence: 99%
“…The opportunity came about due to GCU's involvement in an academic project looking the potential for district heating systems being fed from energy recovered from water in mine workings in and around Glasgow City Centre. This was of interest to the Strathclyde Partnership Transport (SPT) owing the Glasgow Subway, currently manages and removes (via pumping) large volumes from water that ingresses into the tunnels on a daily basis [1,2]. The water ingress causes dampness, corrosion and defects making it a major contributor to ongoing expensive infrastructure maintenance.…”
Section: Introductionmentioning
confidence: 99%